PENGARUH BUDAYA DAN KOMITMEN ORGANISASI SERTA HUBUNGANNYA ANTARA PARTISIPASI PENGANGGARAN DAN KINERJA MANAJERIAL PERUSAHAAN AMDK DI PASURUAN - Wijayanti, Titik (Department of Management, 2012)
PENGARUH BUDAYA DAN KOMITMEN ORGANISASI SERTAHUBUNGANNYA ANTARA PARTISIPASI PENGANGGARAN DANKINERJA MANAJERIAL PERUSAHAAN AMDK DI PASURUANTitik WijayantiMagister Manajemen Universitas Muhammadiyah MalangE-mail: titikwijayanti98@yahoo.comABSTRACKThis study examines the effects of 1) budgetary participation on the managerial performance and 2)organizational culture on moderating relationship between budgetary participation and managerialperformance. This study also examine organizational commitment on moderating the relationshipbetween budgetary participation and managerial performance. This study use data obtained fromAMDK companies in Pasuruan through proportional stratified sampling. This studies? respondentsare middle and lower managers in 20 AMDK companies in Pasuruan, East Java, Indonesia. From120 questionnaires distribute to respondents, only 68 questionnaires were returned and were useablefor analysis a response rate of 56,67 %. The method to analyze data is a moderating regressionanalysis. The results show that budgetary participation has no influence on managerial performance.Organizational culture as moderating variable has no influence on relationship between budgetaryparticipation and managerial performance. Organizational commitment as moderating variable hasa negative influence and significant relationship between budgetary participation and managerialperformance.Keywords: organizational culture, organizational commitment, budgetary participation and managerialperformance